2021
DOI: 10.1016/j.jare.2020.02.013
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen sulfide regulates insulin secretion and insulin resistance in diabetes mellitus, a new promising target for diabetes mellitus treatment? A review

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(37 citation statements)
references
References 77 publications
0
35
0
2
Order By: Relevance
“…OT, CSE and CBS are expressed in insulin-sensitive tissues [ 95 , 96 ]. H 2 S is endogenously released by skeletal muscle, liver, adipose and islet-β-cells [ 97 ]; the OT and OTR are also present in islet-β-cells and skeletal muscle cells [ 98 ]. OT has been reported to increase glucose uptake in cardiomyocytes via PI3K signaling [ 96 ]; exogenous H 2 S administration restored blood glucose levels in the previously mentioned CSEko mice, and was associated with an upregulation of cardiac OTR [ 19 ].…”
Section: Chronic Cardiovascular Diseasementioning
confidence: 99%
“…OT, CSE and CBS are expressed in insulin-sensitive tissues [ 95 , 96 ]. H 2 S is endogenously released by skeletal muscle, liver, adipose and islet-β-cells [ 97 ]; the OT and OTR are also present in islet-β-cells and skeletal muscle cells [ 98 ]. OT has been reported to increase glucose uptake in cardiomyocytes via PI3K signaling [ 96 ]; exogenous H 2 S administration restored blood glucose levels in the previously mentioned CSEko mice, and was associated with an upregulation of cardiac OTR [ 19 ].…”
Section: Chronic Cardiovascular Diseasementioning
confidence: 99%
“…Moreover, metabolomic studies indicate that H 2 S can stimulate the activity of multiple Krebs cycle enzymes [ 56 , 58 ]. H 2 S was also found to upregulate glucose uptake in various cell types [ 171 , 172 , 173 , 174 ]; this may be very important to support the high glucose utilization of the cancer cell. Multiple metabolomic studies and genome wide gene expression studies [ 56 , 58 , 174 ] suggest that endogenously produced H 2 S plays a role in the reprogramming of the pyrimidine and purine metabolism, amino acid metabolism, nicotinate and nicotinamide metabolism, fatty acid metabolism, glutamate metabolism, the urea cycle, and several other pathways.…”
Section: Additional Mitochondrial Roles Of H 2 mentioning
confidence: 99%
“…There is currently a scarcity of studies interrogating the interaction of Acarbose with H 2 S. This presents a potentially fruitful area of novel research as H 2 S is already known to modulate insulin signalling and whole-animal glucose metabolism across tissues, cellular processes that appear intimately linked with longevity [ 141 ]. As with other signalling pathways, the effects of H 2 S are complex, with independent studies reporting either protective or deleterious effects [ 142 ]. The endogenous production of H 2 S in adipose cells was first described by Feng et al [ 143 ] who showed that elevated CSE expression and H 2 S production was correlated with insulin resistance in rats, suggestive of a deleterious diabetic phenotype associated with H 2 S expression in adipocytes.…”
Section: H 2 S and Ageingmentioning
confidence: 99%